Comparative influence of brand, emotional experience and equity on customer satisfaction: a study of iphone and samsung users in islamic business perspective - Aprilia, Desi; Fuadi, Fatih; Ermawati, Liya (Institute of Computer Science (IOCS), 2024)
Sensory brand experience and emotional experience have been recognized as important factors influencing consumer perceptions of brands. On the other hand, brand equity reflects the added value that a brand provides in consumer perceptions and preferences. Customer satisfaction is the main goal for companies in maintaining and increasing customer loyalty. The formulation of the problem in this research is:Are there differences in the influence of Sensory Brand Experience, Emotional Experience, Brand Equity on Customer Satisfaction among iPhone and Samsung Users in Bandar Lampung from an Islamic business perspective? This research aims to compare the influence of Sensory Brand Experience, Emotional Experience, and Brand Equity on Customer Satisfaction among iPhone and Samsung users, using an Islamic business perspective. The research method used is quantitative using a questionnaire as a data collection tool. The research sample was selected purposively from the population of iPhone and Samsung users in Bandar Lampung. The data collected was Two-way ANOVA test to find differences between variables. The results of this research are expected to provide a better understanding of how sensory brand experience, emotional experience, and brand equity contribute to customer satisfaction, especially in the context of using technology products that have an Islamic business dimension. The practical implication of this research is to provide guidance for companies in increasing customer satisfaction by improving brand experience and strengthening their brand equity, in accordance with Islamic business principles which emphasize fairness, transparency and product quality.